Pengembangan LKS Berbantuan Geogebra for Smartphone Mata Kuliah Kalkulus Diferensial pada Materi Pertidaksamaan Fungsi - Aan Subhan Pamungkas; Eka Rachma Kurniasi; Anton (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2020)
The study was conducted due to the unsatisfied results of students’answers and interviews on Differential Calculus material in which the studentsgraphically did not understand the interpretation of a function that was being solved and were not proficient in manipulating algebra, therefore, no solution was found. Based on these findings, a geogebra-assisted worksheet for smartphones was designed to improve students' understanding onthe topic of inequality. This study aimedto develop student worksheets in understanding the topic of inaccuracy in a function. This worksheet consistedof two parts that help students buildingtheir own understanding onthe graphic form of an equation and its solution both graphically and procedurally through algebra. To see the feasibility of the worksheets, expert validation and practicalitytests were conducted to students. The results of the revision were then distributed to 10 Untirta Mathematics Education students who were taking the MK Differential Calculus. Students spent 60 minutes to complete it. They tried to find thesolutions to the problems given with the help of geogebra for smartphones, by firstlysolving them graphically and finding the points referred to in the Cartesian diagram. Then,they solved the problemswith algebraic manipulation as a form of confirmation of the answersobtained. After completing the whole worksheet, it was shownthat the students couldsolve the problems graphically well.points referred to in the Cartesian diagram. Then,they solved the problemswith algebraic manipulation as a form of confirmation of the answersobtained. After completing the whole worksheet, it was shownthat the students couldsolve the problems graphically well.